Mobile Ferrograph System for Ultrahigh Permeability Alloys - Charubin, Tomasz; Nowicki, Michał; Marusenkov, Andriy; Szewczyk, Roman; Nosenko, Anton; Kyrylchuk, Vasyl (Journal of Automation, Mobile Robotics and Intelligent Systems, 2018)
This paper presents a mobile ferrograph system for measurement of magnetic parameters of ultrahigh permeability alloys. The structure of developed system is described, as well as exemplary measurement results of Co67Fe3Cr3B12Si15 alloy used in space applications are presented.